STUDI SPATIAL PERCEPTION DALAM PENYEDIAAN RUANG AKTIVITAS BAGI TUNA RUNGU DI KELAPA GADING - Michael Geraldo; Diah Anggraini (Jurusan Arsitektur dan Perencanaan, 2023)
Every human being must have felt that there is something lacking in them, some people feel lacking because of difficulties and some people are also grounded because of thoughts or psychological influences. Both have a real impact on their own suffering. Having a deficiency of one of our five main senses must have a pretty significant impact. This book is written to discuss one of them, which is the rhetoric on the senses of hearing. Having this hearing impairment can be due to genetic factors (derivatives); congenital (from within the womb); or what we can as long as we live our lives. This prevents recipients from socializing and some people in the community may even stay away from them, because they find it difficult to communicate with them. This can make her suffering feel isolated, fearful, and give up to struggle to live her life. As my fellow humans have a sense of empathy for them, i can imagine how difficult it is for them to live their day-to-day lives in the midst of a civilization that relies on sound as the primary sign or signal to communicate. Then you have to help them and give them the